Considerations in designing systems for large scale production of human cardiomyocytes from pluripotent stem cells - Chen, Allen (BioMed Central, 2014)
Human pluripotent stem cell (hPSC)-derived cardiomyocytes have attracted attention as an unlimited source of cells for cardiac therapies. One of the factors to surmount to achieve this is the production of hPSC-derived cardiomyocytes at a commercial or clinical scale with economically and technically feasible platforms. Given the limited proliferation capacity of differentiated cardiomyocytes and the difficulties in isolating and culturing committed cardiac progenitors, the strategy for cardiomyocyte production would be biphasic, involving hPSC expansion to generate adequate cell numbers followed by differentiation to cardiomyocytes for specific applications. This review summarizes and discusses up-to-date two-dimensional cell culture, cell-aggregate and microcarrier-based platforms for hPSC expansion. Microcarrier-based platforms are shown to be the most suitable for up-scaled production of hPSCs. Subsequently, different platforms for directing hPSC differentiation to cardiomyocytes are discussed. Monolayer differentiation can be straightforward and highly efficient and embryoid body-based approaches are also yielding reasonable cardiomyocyte efficiencies, whereas microcarrier-based approaches are in their infancy but can also generate high cardiomyocyte yields. The optimal target is to establish an integrated scalable process that combines hPSC expansion and cardiomyocyte differentiation into a one unit operation. This review discuss key issues such as platform selection, bioprocess parameters, medium development, downstream processing and parameters that meet current good manufacturing practice standards.